2016
DOI: 10.1080/00268976.2016.1198503
|View full text |Cite
|
Sign up to set email alerts
|

Generalising the mean spherical approximation as a multiscale, nonlinear boundary condition at the solute–solvent interface

Abstract: In this paper, we extend the familiar continuum electrostatic model to incorporate finite-size effects in the solvation layer, by perturbing the usual macroscopic interface condition. The perturbation is based on the mean spherical approximation (MSA), to derive a multiscale solvation-layer interface condition (SLIC/MSA). We show that SLIC/MSA reproduces MSA predictions for Born ions in a variety of polar solvents, including water as well as other protic and aprotic solvents. Importantly, the SLIC/MSA model pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In this work, we have demonstrated that a simple implicit-solvent model, composed of the traditional surface-area-dependent nonpolar model plus the modified continuum dielectric model SLIC for the electrostatics, predicts solvation free energies and entropies with surprising accuracy for both neutral and charged small molecules. This result represents the joining of two previous studies of SLIC, one on solvation thermodynamics for spherical ions [36,45] and one on the solvation free energies of complex polyatomic solutes [26,35] . We note that our model does not explicitly account for either hydrogen bonding or other solvent structure [63,64] , and reproduces solvation thermodynamics in both hydrogen-bonding and non-hydrogen-bonding solvents [36] .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In this work, we have demonstrated that a simple implicit-solvent model, composed of the traditional surface-area-dependent nonpolar model plus the modified continuum dielectric model SLIC for the electrostatics, predicts solvation free energies and entropies with surprising accuracy for both neutral and charged small molecules. This result represents the joining of two previous studies of SLIC, one on solvation thermodynamics for spherical ions [36,45] and one on the solvation free energies of complex polyatomic solutes [26,35] . We note that our model does not explicitly account for either hydrogen bonding or other solvent structure [63,64] , and reproduces solvation thermodynamics in both hydrogen-bonding and non-hydrogen-bonding solvents [36] .…”
Section: Discussionsupporting
confidence: 68%
“…As the charging free energy from λ = 0 to λ = δ is very small compared to the charging free energy over the remaining interval, the charging integral can be approximated as the integral from λ = δ to λ = 1, allowing the use of the familiar linear-response expression. Readers interested in further details are referred to earlier work [26,35,36,44,45] . A critical assessment of these approximations is a subject of ongoing work.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests an alternative approach in which a physically meaningful, effective modification should be employed in the interface condition, rather than changing the interface directly (via the atom radii). 24,26,27,45 The asymmetric response can be described as a combination of two distinct different mechanisms. 24 The first one, as it was described above, is the steric asymmetry and the other one is the electrostatic interface potential that persists even if the solute is uncharged.…”
Section: Introductionmentioning
confidence: 99%